Characterization and experimental validation of reconfigurable optical adddrop multiplexers for next generation network - Al Sayeed, Choudhury Abdullah (University of Ottawa (Canada), 2006)
This thesis proposes a detailed design layout for the next generation optical metropolitan network to be equipped with Reconfigurable Optical Add/Drop Multiplexer (ROADM) subsystems. It demonstrates the key features of ROADM subsystems including the development of ring-to-ring interconnection in optical domain. Simulation models are developed for the ROADM subsystems that can easily be configured according to the devices' available specification sheet. The developed simulation models have been verified with experimental measurements obtained from a reconfigurable all-optical metro network testbed. Such simulation modules will be valuable in planning and designing the next generation metro optical networks. Combining the outcome of the research results presented in the thesis, a hybrid reconfigurable add/drop module is proposed. The proposed hybrid architecture can achieve lower loss among the existing 3rd generation ROADM modules. The functionality of ROADMs can also be improved by an Intelligent ROADM subsystem proposed for the next generation dynamically provisioned wavelength network.
Keywords: Engineering, Electronics and Electrical.